2014 Joint IEEE International Symposium on the Applications of Ferroelectric, International Workshop on Acoustic Transduction M 2014
DOI: 10.1109/isaf.2014.6917885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of curing procedures on the electrical properties of epoxy-based isotropic conductive adhesives

Abstract: In this paper, a typical isotropic conductive adhesives (ICAs) composed of an epoxy-based binder containing micro-sized silver flakes was prepared and the effects of different curing procedures on the electrical properties of conductive adhesives were investigated. The results showed that there a greater influence of the curing temperature on 55% silver fill loading, the volume resistivity of ICAs decreased to 4.7×10 -3 from 1.0×10 -3 cured at 180 0 C and 250 0 C, respectively. However, there is almost no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Lately, resistance monitoring technology has been applied to study the curing process of epoxybased ICA [11][12][13][14], while such study on SSP sintering process is not found. Inoue et al [11,13,14] found that the change of electrical conductivity can not only be caused by curing reaction of the binder molecules, but also the conductivity change of the inter-filler chemicals, by comparing resistance signals with results from free-damped oscillation method.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…Lately, resistance monitoring technology has been applied to study the curing process of epoxybased ICA [11][12][13][14], while such study on SSP sintering process is not found. Inoue et al [11,13,14] found that the change of electrical conductivity can not only be caused by curing reaction of the binder molecules, but also the conductivity change of the inter-filler chemicals, by comparing resistance signals with results from free-damped oscillation method.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Xiong et al [12] obtained resistance-time curve with ICAs of 65 wt% silver fill loading. The resistance value becomes detectable (< 2.0 MΩ) at 27 min.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations